Intrastate conflicts and international humanitarian intervention: case studies in Indonesia - Situmorang, Mangadar (Curtin University, 2007)
The differences in the international responses to the violent conflicts in East Timor (1998–1999), Maluku (1999–2003) and Aceh (1998–2005) are examined in this research. Given the growing acceptance of the significance of the use of military force for humanitarian purposes, the humanitarian crises in Maluku and Aceh might prima facie have justified humanitarian intervention similar to that in East Timor. By analysing the differences from the Indonesia’s domestic political point of view it is clear that the conscience-shocking situation caused by the violent conflicts was not the compelling factor for the international community to militarily intervene. The deployment of a multinational force in East Timor (INTERFET) was decided only after the UN and foreign major countries believed that such military intervention would not jeopardize the ongoing process of democratization in Indonesia. This suggested that Indonesia’s domestic circumstance was central to whether a similar measure in Maluku and Aceh would take place or not. Due to the reformasi (political reform) in Indonesia within which the independence of East Timor took place, two main changes within Indonesian politics, namely the growing sentiment of anti-international intervention and the continuing democratization process, helped to ensure that humanitarian intervention in the two other regions did not happen.These two conditions were fortified by the increasingly consolidated democratic politics which brought the communal conflict in Maluku to the Malino Peace Agreement. The emergence of a stronger and democratic government in Indonesia, furthermore, made cooperation with the international community possible in seeking a peaceful resolution to the armed conflict in Aceh. By involving the Crisis Management Initiative (CMI) the government of Indonesia and the Free Aceh Movement (GAM) agreed to the Helsinki peace agreement and accepted the role of the Aceh Monitoring Mission (AMM) to secure its implementation. Thus, a strong democratic government made an international military intervention for humanitarian purposes unnecessary.